2007
DOI: 10.1038/nbt1299
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplastic photorespiratory bypass increases photosynthesis and biomass production in Arabidopsis thaliana

Abstract: We introduced the Escherichia coli glycolate catabolic pathway into Arabidopsis thaliana chloroplasts to reduce the loss of fixed carbon and nitrogen that occurs in C(3) plants when phosphoglycolate, an inevitable by-product of photosynthesis, is recycled by photorespiration. Using step-wise nuclear transformation with five chloroplast-targeted bacterial genes encoding glycolate dehydrogenase, glyoxylate carboligase and tartronic semialdehyde reductase, we generated plants in which chloroplastic glycolate is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
395
6
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(427 citation statements)
references
References 47 publications
17
395
6
3
Order By: Relevance
“…The production of 2-PG is a consequence of Rubisco's catalytic bifunctionality that sees it not only catalyze the productive carboxylation of ribulose-P 2 into two molecules of 3-phosphoglycerate (3-PGA), but also the oxygenation of ribulose-P 2 producing one 3-PGA and one 2-PG molecule. The 2-PG is considered a waste product since its recycling via photorespiration is energetically demanding and also reduces net carbon assimilation due to CO 2 release during Gly decarboxylation in the mitochondria (Wingler et al, 2000;Kebeish et al, 2007). The catalytic properties of Rubisco therefore play a critical, frequently rate-limiting, role in photosynthetic carbon assimilation and have a pervasive influence on the efficiency with which plants uses their resources of light, water, and nitrogen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The production of 2-PG is a consequence of Rubisco's catalytic bifunctionality that sees it not only catalyze the productive carboxylation of ribulose-P 2 into two molecules of 3-phosphoglycerate (3-PGA), but also the oxygenation of ribulose-P 2 producing one 3-PGA and one 2-PG molecule. The 2-PG is considered a waste product since its recycling via photorespiration is energetically demanding and also reduces net carbon assimilation due to CO 2 release during Gly decarboxylation in the mitochondria (Wingler et al, 2000;Kebeish et al, 2007). The catalytic properties of Rubisco therefore play a critical, frequently rate-limiting, role in photosynthetic carbon assimilation and have a pervasive influence on the efficiency with which plants uses their resources of light, water, and nitrogen.…”
mentioning
confidence: 99%
“…Significant biotechnological effort and expense is being devoted to engineering improvements to CO 2 assimilation in C 3 plants using various strategies (for review, see Raines, 2006;Parry et al, 2007), with recent success coming by transplanting the glycolate catabolic pathway from Escherichia coli into Arabidopsis (Arabidopsis thaliana) chloroplasts that localized recycling of 2-phosphoglycolate (2-PG) to glycerate in the stroma, thereby increasing the CO 2 levels around the photosynthetic CO 2 -fixing enzyme, Rubisco (Kebeish et al, 2007). The production of 2-PG is a consequence of Rubisco's catalytic bifunctionality that sees it not only catalyze the productive carboxylation of ribulose-P 2 into two molecules of 3-phosphoglycerate (3-PGA), but also the oxygenation of ribulose-P 2 producing one 3-PGA and one 2-PG molecule.…”
mentioning
confidence: 99%
“…These approaches include elevating the CO 2 concentration within chloroplasts using recombinant CO 2 /HCO 3 − transporters from cyanobacteria or engineering alternative pathways to bypass photorespiration and release CO 2 within the stroma (13,14). Although each strategy faces continuous challenges in its fine tuning and integration into crops, further improvements in yield and in the efficiency of water and nitrogen use are likely by concurrently "speeding up" rubisco (9).…”
mentioning
confidence: 99%
“…When researchers tried to introduce this bacterial mechanism into Arabidopsis, they found that photosynthesis was boosted only modestly 3 . Ort suspects that this is because plant cells were still shipping glycolate out of the chloroplast even with the introduction of the improved chemical pathway.…”
Section: Carbon Fixmentioning
confidence: 99%